2021
DOI: 10.1002/srin.202100520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B2O3 on the Melt Structure and Viscosity of CaO–SiO2 System

Abstract: Molecular dynamics (MD) simulations have been used to study the structure properties of CaO–SiO2 slags and CaO–SiO2–B2O3 slags with different basicity. The results show that the addition of B2O3 to the higher basicity system of CaO–SiO2 (basicity >1.12) increases the degree of polymerization (DOP) of the system and the complexity of network structures, theoretically leading an increase in the viscosity of the slag. In the CaO–SiO2–B2O3 ternary system, the structure of Si–BO (bridging oxygen)–B is more dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The results showed that when Fe t O <10 wt%, the viscosity is only related to the basicity, and when Fe t O >10 wt%, the viscosity decreases regardless of the basicity. Zhang's [17] research showed that the addition of B 2 O 3 in the case of high basicity (basicity >1.12) will increase the degree of polymerization, increasing the viscosity of the slag. Zhang's [18] research showed that with increasing B 2 O 3 content from 0 wt% to 4 wt%, the viscosity of FeO-MgO-SiO 2 slag system decreased, the break temperature decreased by 98°C, and the apparent activation energy decreased by 16 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that when Fe t O <10 wt%, the viscosity is only related to the basicity, and when Fe t O >10 wt%, the viscosity decreases regardless of the basicity. Zhang's [17] research showed that the addition of B 2 O 3 in the case of high basicity (basicity >1.12) will increase the degree of polymerization, increasing the viscosity of the slag. Zhang's [18] research showed that with increasing B 2 O 3 content from 0 wt% to 4 wt%, the viscosity of FeO-MgO-SiO 2 slag system decreased, the break temperature decreased by 98°C, and the apparent activation energy decreased by 16 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%